Concepts and applications (New York, 2002)
Chemistry: Concepts and Applications is a comprehensive chemistry program that provides an intuitive conceptual approach to developed core concepts for a first year high school chemistry curriculum. The use of quantitative ideas is appropriate to enable students to practice and master to understand the full application of chemistry. The text design is student friendly that utilizes vivid visuals and clear narrative that incorporates everyday analogies related to student's interest.
Keywords: Chemistry,Hóa học